A Soft-Decision State-Space Equalizer for FIR Channels - Thielecke, Jörn (IEEE Transactions on Communications, 1997)
A nonlinear equalizer for binary data transmission over linitc impulse response channels is developed. It is based on a state-space description of the channel. The equations of the resulting algorithm resemble the equations of a Kaiman harddecision feedback equalizer, similar to the one of McLaughlin et al. However, the derivation of the equalizer differs significantly from the derivation of the Kaiman algorithm. Particularly, probability estimates of the received bits are incorporated. They can be exploited in several ways to improve the performance of the equalizer and of the complete transmission system. Simulations for a mobile radio channel show that the new equalizer is an alternative to well-established equalizers like the Viterbi or the conventional hard-decision feedback equalizer. © 1997 IEEE.
UnivIS-Import:2015-03-05:Pub.1997.tech.IE.komele.asoftd